Characteristics of the obesogenic environment around schools are associated with body fat and low-grade inflammation in Brazilian children - Mariana De Santis Filgueiras; Milene Cristine Pessoa; Josefina Bressan; Aline Siqueira Fogal Vegi; Ariene Silva do Carmo; Fernanda Martins de Albuquerque; Danielle Soares Gardone; Juliana Farias de Novaes (Cambridge University Press, 2023)
Abstract Objective: To assess the association of obesogenic environmental characteristics around schools with body adiposity and adipokine concentrations in Brazilian children. Design: Cross-sectional study. Body adiposity was assessed using the dual-energy X-ray absorptiometry. Concentrations of leptin, adiponectin, retinol-binding protein 4 (RBP4) and chemerin were measured. Predominantly ultra-processed food (UPF) stores, public physical activity (PA) facilities, green spaces, walkability, traffic accidents and crime were evaluated. The neighbourhood unit was the 400 m (0·25 miles) road network buffer around schools. The association of environmental characteristics with body adiposity and adipokine concentrations was assessed by linear regression models using generalised estimating equations. Setting: Urban schools (n 24), Viçosa, Minas Gerais, Brazil. Participants: Children aged 8 and 9 years (n 378). Results: A higher density of predominantly UPF stores and a lower percentage of green space were associated with higher total (β: 0·12; 95 % CI 0·06, 0·18 and β: -0·10; 95 % CI -0·16, -0·04, respectively) and android body fat (β: 0·28; 95 % CI 0·13, 0·43 and β: -0·18; 95 % CI -0·32, -0·04, respectively). In addition, the densities of PA facilities and crime were inversely associated with leptin concentrations. Traffic accidents density and percentage of green spaces around schools had, respectively, a positive and an inverse association with concentrations of adiponectin and RBP4. Conclusions: Obesogenic environmental characteristics around schools were associated with total and android body fat, as well as with pro-inflammatory adipokine concentrations in Brazilian children from a medium-sized city.